In zijn werkkamer op het Rotterdamse stadhuis. Uit: Stz N 183, tussen p. 192 en 193. Zie ook BG B2/199 - Wolf, Jules H.,
In zijn werkkamer op het Rotterdamse stadhuis. Uit: Stz N 183, tussen p. 192 en 193. Zie ook BG B2/199.